Comprehensive review on use of phospholipid based vesicles for phytoactive delivery. (3rd July 2022) - Gupta, Manish Kumar; Sansare, Vipul; Shrivastava, Birendra; Jadhav, Santosh; Gurav, Prashant
Abstract: Plant-derived phytoconstituents are well known for their therapeutic potential. It has been experimentally demonstrated that whole-plant extract or isolated phytoconstituents reveal various therapeutic potentials like hepatoprotective, antimicrobial, neuroprotective, antitumor, antioxidant, skin protectives, etc. Although these phytoconstituents have potential therapeutic benefits, their use is limited due to their poor bioavailability, stability in biological fluids, and authentication issues. These continue to be an open problem that affects the application of these valuable ancient herbal herbs in the effective treatment and management of various disease conditions. A potential solution to these difficult problems could be the loading of phytoactives in phospholipid-based vesicular systems. Phospholipid-based vesicles like liposomes, phytosomes, ethosomes as well as transfersomes were effectively utilized recently to solve drawbacks and for effective delivery of phytoactives. Several landmark studies observed better therapeutic efficacy of phytoactive loaded vesicles compared to conventional drug delivery. Thus phospholipid-based vesicles mediated phytoactive delivery is a recently developed promising and attractive strategy for better therapeutic control on disease conditions. The present short review highlights recent advances in herbal bioactive loaded phospholipid-based vesicles.